Form, Structure of Music in Magic Genjring Art at Randusanga Kulon Village, Brebes District, Brebes Regency - Prasetyo, Nandhy; Sumaryanto, Totok; Sunarto, Sunarto (Catharsis, 2019)
Magic Genjring is an art handed down from generation to generation in Randusanga Kulon Village, Brebes District, Brebes Regency. However, in 1968 this art experienced changes that could be considered very significant. So that researchers are very interested in analyzing the shape, structure of this musical art and find out the function of each instrument used. The method used in this research is qualitative descriptive, with an interdisciplinary approach to sociology and music science. While the data collection technique used observation, interviews, and document studies, the validity technique itself used triangulation, the data analysis technique is collecting the data from observations, interviews, and documentation, then it is reduced to sorting the data that supports the research until finally concluded. The results of the analysis of the shape of the musical structure are described as follows: the magic Genjring song consists of 4 motifs, 2 phrases (both question and answer sentences), the song starts from the 6th chord with Do = C, ie (am), with progress to the chord ii (dm). The beat or beat value uses ¾, then changes in the middle of the song to 4/4 in the 9th to 10th bar with percussion accent markers and changes 2/4 until returning to the initial sukat ¾. One of the factors that caused the change in shape, the structure of the music was due to the provision of extensive improvisation so that no patent standard. The results of this study are expected to become a serious concern, especially for senior artists, so that in the future it can be easier to reduce the next generation related to music because they already have a grip. Appreciation from related agencies and residents as art owners.